Pengaruh Metode Talking Stick dalam Model Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar Peserta Didik Kelas XI MIA SMA Negeri 10 Gowa (Studi pada Materi Pokok Larutan Penyangga) - Pince Salempa; Feby Indayani; Muhammad Anwar (ChemEdu, 2022)
This research was a quasi-experiment research that aimed to know the effect of Talking Stick Method in Guided Inkuiry Model Towards Chemistry Learning Outcomes of Class XI MIA SMA Negeri 10 Gowa on Buffer Solution Subject Matter. The post-test only control group design was used in this research. The Sample was taken randomly. Result of prerequisite analysis for inferential statistic show that the data of experiment and control class was not distributed normally and it has homogeny variance. So, Man-Withney parametric test with ∝=0.05 was used with yield z calculated; 3,27 > z table 1.64. It can be concluded that H0 rejected and H1 accepted which means that there is an effect of talking stick method in guided inkuiry model towards chemistry learning outcomes of class XI MIA SMA Negeri 10 Gowa on buffer solution subject matter.